Efektivitas Penggunaan Alat Up Sonic dalam Mengoptimalkan Proses Pembakaran Berbagai Jenis Material - Siti Robiah Adawiyah; Izza Shoffa; Walsatul Kurnia; Septiani Makrifatus Sholehah; Tyas Fitriana; Sabrina Fida Shafira; Fernando Redondo; Okta Fiana; Tiara Indah Mawarni; Muhammad Kusnen; Reiko Apriliyadi; Naeli Mahda Mazaya; Ahmad Nurul Hadi Ramdhani; Rifqi Fahrulrozi (Lembaga Pengembangan Kinerja Dosen, 2025)
This report discusses the effectiveness of the Up Sonic tool in optimizing the combustion process of various types of materials. Up Sonic is an innovative technology designed to enhance combustion efficiency and reduce harmful gas emissions. The study examines the performance of this tool on different materials, including fossil fuels and biomass. The results indicate that the use of Up Sonic can accelerate the combustion process, improve energy efficiency, and reduce carbon emissions. Therefore, this tool has the potential to become a sustainable solution in the combustion and energy industry.